Review of the Mechanisms by Which Transcription Factors and Exogenous Substances Regulate ROS Metabolism under Abiotic Stress - Peng Liu; Xiaolei Wu; Binbin Gong; Guiyun Lü; Jingrui Li; Hongbo Gao (Antioxidants, 2022)
Reactive oxygen species (ROS) are signaling molecules that regulate many biological processes in plants. However, excess ROS induced by biotic and abiotic stresses can destroy biological macromolecules and cause oxidative damage to plants. As the global environment continues to deteriorate, plants inevitably experience abiotic stress. Therefore, in-depth exploration of ROS metabolism and an improved understanding of its regulatory mechanisms are of great importance for regulating cultivated plant growth and developing cultivars that are resilient to abiotic stresses. This review presents current research on the generation and scavenging of ROS in plants and summarizes recent progress in elucidating transcription factor-mediated regulation of ROS metabolism. Most importantly, the effects of applying exogenous substances on ROS metabolism and the potential regulatory mechanisms at play under abiotic stress are summarized. Given the important role of ROS in plants and other organisms, our findings provide insights for optimizing cultivation patterns and for improving plant stress tolerance and growth regulation.